2017
DOI: 10.3390/app7040347
|View full text |Cite
|
Sign up to set email alerts
|

Tangible User Interface and Mu Rhythm Suppression: The Effect of User Interface on the Brain Activity in Its Operator and Observer

Abstract: The intuitiveness of tangible user interface (TUI) is not only for its operator. It is quite possible that this type of user interface (UI) can also have an effect on the experience and learning of observers who are just watching the operator using it. To understand the possible effect of TUI, the present study focused on the mu rhythm suppression in the sensorimotor area reflecting execution and observation of action, and investigated the brain activity both in its operator and observer. In the observer exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Similarly, in other classes (left hand and right foot), EEG activities of poor performers were similar to those of good performers. Previous studies reported that somatosensory stimuli, which differs in its pattern or type, induces other patterns of cortical activity [63], [64], [65], [66]. In addition, imagery and execution of somatosensory stimulation can facilitate cortical excitability [67], [68].…”
Section: Novel Hybrid-approach To Enhance Bci Performance In Bci-inef...mentioning
confidence: 97%
“…Similarly, in other classes (left hand and right foot), EEG activities of poor performers were similar to those of good performers. Previous studies reported that somatosensory stimuli, which differs in its pattern or type, induces other patterns of cortical activity [63], [64], [65], [66]. In addition, imagery and execution of somatosensory stimulation can facilitate cortical excitability [67], [68].…”
Section: Novel Hybrid-approach To Enhance Bci Performance In Bci-inef...mentioning
confidence: 97%
“…The game components are the tangible user interface that helps to connect the game and the players as they would immerse in the game session (Isoda et al, 2017).…”
Section: Framework Of the Simulation Board Gamementioning
confidence: 99%
“…Moreover, needs differ as the disabilities vary; each disabled person may need different assistive input devices depending on their disabilities. Thence, different command input mediums were discussed, such as the medium of voice-controlled hands-free [19] and the brain-computer interface (BCI) communication pathway [20,21]. Shinde et al developed an Arduino-based application including an android application, a wireless module, and Arduino devices to control smart appliances [22].…”
Section: Introductionmentioning
confidence: 99%